Islamisasi Ilmu versus Dekolonial: Kerangka Kriteria Pembeda dalam Epistemologi Islam Kontemporer - Samsudin Buamona B (JUANGA: Jurnal Agama dan Ilmu Pengetahuan, 2026)
The Islamization of knowledge project and the decolonial approach are frequently conflated in contemporary Islamic epistemology discourse, despite emerging from distinct intellectual genealogies with fundamentally different philosophical consequences. This conflation directly affects curriculum development in Islamic higher education, as administrators struggle to maintain consistent references when both terms are applied interchangeably without clear conceptual boundaries. This study develops systematic criteria to differentiate the two projects through a critical literature review of primary texts by al-Faruqi, al-Attas, Quijano, and Mignolo alongside relevant academic literature. The analysis examines five comparative dimensions: intellectual genealogy, epistemological foundations, methodological strategy, orientation toward tradition and modernity, and sociopolitical transformative vision. Findings indicate that the Islamization project remains normative-theological with revelation as its highest authority, while the decolonial approach is pluralist and rejects any singular epistemic authority. This study offers a reusable criteria framework enabling scholars and Islamic higher education administrators to position epistemological projects more precisely, thereby avoiding conceptual conflation that persists in curricula and institutional policy